Innovation Utilization of Digital Applications Efforts to Improve College Achievement of Civil Engineering Students - Honesti, Leli; Manurung, Edison Hatoguan; Sitindaon, Charles; Indarwanto, Muji; Puro, Sarjono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This paper intended to discuss what experts say about innovating digital applications to improve student achievement in civil engineering in digital days was essential. The author believes that one of the innovative solutions to improve learning outcomes is using technology applications in both teaching and evaluation. The reason is that technological innovation can transform learning compared to traditional strategies. To complete the discussion of the above issues, we will conduct a series of data searches with the help of electronic searches on databases of journals and books published by several publications with international reputations such as Elsevier, ERIC, Google Book, Taylor & Francis, and other database sources published ten years ago. Furthermore, data analysis involves a phenomenology approach. We explored as much data as possible until we could answer the above problems with high validity and reliability. Our study involved data coding systems, evaluation, and interpretation of in-depth data, and concluding. Based on the existing data, we can conclude that the use of digital technology applications can improve the learning outcomes of civil engineering students. Digital technology serves as a means of conveying, obtaining, processing, and communicating information more effectively than the classical methods that have been used so far, especially in the case of work involving civil engineering work systems